KHAZANAH NASKAH ALQURAN KOLEKSI MUSEUM ADITYAWARMAN: DESKRIPSI DAN KEKHASANNYA - Pramono, Pramono (Jurnal Al- Ma'arif : Ilmu Perpustakaan dan Informasi Islam, 2021)
ABSTRACT One of the official institutions that collect Minangkabau manuscripts is Adityawarman Museum. In this museum, there are 94 bundles of manuscripts with various texts, such as fiqh, tawhid, sufism, hadith, amulet, tambo, Qur'an, literature, history, arabic grammar, and interpretation. Among the collection, there are seventeen bundles of Qur'anic manuscripts that have uniqueness and distinctiveness. Its uniqueness and distinctiveness are characterized by the existence of a note on the margins that explain the information of the improvement of the Qur'anic meaning. The note also informs about the word or sentence left behind in a verse. This phenomenon signifies that the tradition of tahqiq (deciding the truth with evidence) in the manuscript of the Qur'an has become a tradition in Minangkabau Surau of the past. Keywords: manuscript, Alquran, Muzeum of Adityawarman, tahqiq, Minangkabau. ABSTRAK Salah satu lembaga resmi yang mengoleksi naskah Minangkabau adalah Museum Adityawarman. Di museum ini terdapat 94 bundel naskah dengan beragam teks, seperti fikih, tauhid, tasawuf, hadis, azimat, tambo, Alquran, sastra, sejarah, gramatikal Arab, dan tafsir. Di antara koleksi tersebut, terdapat tujuh belas bundel naskah Alquran yang memiliki keunikan dan kekhasan. Keunikan dan kekhasannya ditandai dengan adanya catatan pada pias yang menerangkan informasi perbaikan matan mushaf Alquran. Catatan tersebut juga menginformasikan berkenaan dengan kata atau kalimat yang tertinggal dalam satu ayat. Fenomena ini menandakan bahwa tradisi tahkik dalam manuskrip mushaf Alquran telah menjadi tradisi di surau-surau Minangkabau masa lampau. Keywords: manuscript, Alquran, Muzeum of Adityawarman, tahqiq, Minangkabau.